Methicillin-Resistant Staphylococcus aureus Nasal Swab and Suction Drain Tip Cultures in 4573 Spinal Surgeries: Efficacy in Management of Surgical Site Infections. Issue 7 (1st April 2018) - Kawabata, Atsuyuki; Sakai, Kenichiro; Sato, Hirokazu; Sasaki, Shinichi; Torigoe, Ichiro; Tomori, Masaki; Yuasa, Masato; Matsukura, Yu; Arai, Yoshiyasu
Abstract : Study Design: A retrospective single-center study. Objective: To assess the diagnostic value of methicillin-resistant Staphylococcus aureus (MRSA) nasal swab and suction drain tip cultures. Summary of Background Data: The prognostic value of MRSA nasal swab and suction drain tip cultures has not been firmly established in spinal surgery. Methods: This study retrospectively included 4573 consecutive patients who underwent spinal surgery between January 2008 and December 2014. Patients diagnosed with infectious disease were excluded. Prophylactic antibiotics were administered intraoperatively and postoperatively for 48 hours. MRSA nasal swab cultures were taken from all patients before surgery. Drains were removed when the volume of postoperative fluid drainage was less than 50 mL in the preceding 24 hours and cultures were made. Surgical site infection (SSI) was defined according to Centers for Disease Control and Prevention criteria. Results: SSI was identified in 94 cases (2.1%) and bacteria were isolated in 87 cases (92.6%). Positive MRSA nasal swab cultures were identified in 49 cases (1.1%). There was no significant difference in the SSI positivity rate between the MRSA nasal swab culture (+) and (−) groups. Positive drain tip cultures were found in 382 cases (8.4%), 28 of which developed SSI. There was a significant difference in the SSI positivity rate between the drain tip culture (+) and (−) groups. The sensitivity of drain tip culture was 29.8% and the specificity was 92.1%. In 16 of the 28 patients in the SSI (+) group with positive drain cultures, the same bacteria were isolated from the surgical site, giving a bacteria matching rate of 57.1%. Conclusion: MRSA nasal swab and drain tip cultures were not useful for predicting SSI. However, drain tip culture had a high positivity rate in the SSI group and the coincidence rate for the causative pathogen was relatively high. Level of Evidence: 4